Evaluating the alignment of the intended and enacted school-based social studies curricula using Seitz's methodological framework - Guintu, Emie Joane M.; Fajardo, Amelia C.; Calingasan, Lorina Y.; Muega, Maricris B. Acido (Quezon City College of Education, University of the Philippines Diliman, 2020)
This study determined whether Seitz's methodological framework could be used to evaluate the alignment between intended and the enacted school-based curricula of Araling Panlipunan 3 in the Philippine setting. In this intended curriculum, the cognitive processes called for by the learning competencies were determined using the Delphi method while for the enacted curriculum, data was gathered using classroom observations, teacher survey, lesson plans, and teacher interview. The results of the study show that for the content dimension, there is 100% alignment between the intended and the enacted curricula, and for the cognitive process dimension, there is only 57.89% alignment between the intended and the enacted curricula. Through this study, the usefulness of Seitz's methodological framework was examined using the following parameters: process, achievement of goal, and case of use of practicality.
Thesis (Master of Arts in Education - Curriculum Studies)--University of the Philippines, Diliman
Includes bibliographical references (pages 92-99)
Keywords: Social studies -- Study and teaching (Elementary) -- Philippines; Curriculum planning -- Philippines; Curriculum change -- Philippines